Structural Changes of Seagrass Seascapes Driven by Natural and Anthropogenic Factors: A Multidisciplinary Approach - Abadie, Arnaud; Richir, Jonathan; Lejeune, Pierre; Leduc, Michèle; Gobert, Sylvie (Frontiers in Ecology and Evolution, 2019)
Seascape ecology has been widely applied to marine habitats, including seagrass meadows, through various approaches all over the world for the past 30 years. However, these methods mainly study seagrass meadows on a single spatial scale and monitor a single driver of heterogeneity. In addition, few assess the seascape’s structural evolution. This creates gaps between the scientific data provided and those required by environmental managers and stakeholders in charge of seagrass meadow conservation. To meet their expectations, we developed in this paper a new multidisciplinary approach based on the coupling of mapping techniques, particle flux and biometric investigations in a Mediterranean Bay, the Calvi Bay (Corsica, France), to assess the structural evolution of Posidonia oceanica (L.) Delile meadows subject to disturbances. We focused our investigations on the structural characteristics, the spatial dynamics and the particle fluxes of natural sand areas generated by bottom currents and dead matte patches ensued from anchoring damages at 10, 15 and 20 m depth. Natural sand patches and anchoring patches differed in size, the first the largest. They also displayed different erosion-colonization dynamics. Natural sand patches were eroded at a mean speed of 12 cm.a-1 and colonized at a rate of 7 cm.a-1. Anchoring patches showed a mean erosion speed of 3.5 cm.a-1 and a colonization rate of 6.5 cm.a-1. Regarding particle fluxes, continuous meadow and natural patch sedimentation and resuspension rates were 3.7 gDW.m-2.d-1 and 4.1 gDW.m-2.d-1 in average, respectively. In contrast, anchoring patches at 20 m depth acted as sediment traps (112.60 gDW.m-2.d-1 in winter) and showed a higher particle resuspension rate. Our results highlighted the dichotomous dynamics of seagrass seascapes influenced by natural and anthropogenic factors (here anchoring). With an upscaling approach, together with the newest mapping tools of marine habitats, we suggest a new method to study the evolution of seagrass meadows at a large spatial scale. Due to the slow growth of P. oceanica and the centimetric annual evolution of patches revealed in the present study, it is obvious that a metric positioning accuracy is not sufficient to properly investigate the spatial evolution of P. oceanica seascapes.